New Alkoxy Flavone Derivatives Targeting Caspases: Synthesis and Antitumor Activity Evaluation - Joana Moreira; Diana Ribeiro; Patrícia M. A. Silva; Nair Nazareth; Madalena Monteiro; Andreia Palmeira; Lucília Saraiva; Madalena Pinto; Hassan Bousbaa; Honorina Cidade (Molecules, 2018)
The antitumor activity of natural flavonoids has been exhaustively reported. Previously it has been demonstrated that prenylation of flavonoids allows the discovery of new compounds with improved antitumor activity through the activation of caspase-7 activity. The synthesis of twenty-five flavonoids (4–28) with one or more alkyl side chains was carried out. The synthetic approach was based on the reaction with alkyl halide in alkaline medium by microwave (MW) irradiation. The in vitro cell growth inhibitory activity of synthesized compounds was investigated in three human tumor cell lines. Among the tested compounds, derivatives 6, 7, 9, 11, 13, 15, 17, and 18 revealed potent growth inhibitory activity (GI50 < 10 μM), being the growth inhibitory effect of compound 13 related with a pronounced caspase-7 activation on MCF-7 breast cancer cells and yeasts expressing human caspase-7. A quantitative structure-activity relationship (QSAR) model predicted that hydrophilicity, pattern of ring substitution/shape, and presence of partial negative charged atoms were the descriptors implied in the growth inhibitory effect of synthesized compounds. Docking studies on procaspase-7 allowed predicting the binding of compound 13 to the allosteric site of procaspase-7.